2014
DOI: 10.2337/db13-1382
|View full text |Cite
|
Sign up to set email alerts
|

Low HERV-K(C4) Copy Number Is Associated With Type 1 Diabetes

Abstract: Complement component C4 (C4) is a highly variable complement pathway gene situated ∼500 kb from DRB1 and DQB1, the genes most strongly associated with many autoimmune diseases. Variations in C4 copy number (CN), length, and isotype create a highly diverse gene cluster in which insertion of an endogenous retrovirus in the ninth intron of C4, termed HERV-K(C4), is a notable component. We investigated the relationship between C4 variation/CN and type 1 diabetes. We found that individuals with type 1 diabetes have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 24 publications
1
28
1
Order By: Relevance
“…To date, only a recent publication links the low number of HERV-K copies within the C4 gene cluster to an increased risk of developing T1D. The authors suggest that the endogenous retroviral insertion could offer protection against T1D, but they did not provide any functional relationship between the low copy numbers and the T1D susceptibility (59). Conversely, present results now clearly indicate the involvement of an endogenous retrovirus, HERV-W, in the pathogenesis of T1D.…”
Section: Endogenous Retroviruses In T1d Etiologycontrasting
confidence: 40%
“…To date, only a recent publication links the low number of HERV-K copies within the C4 gene cluster to an increased risk of developing T1D. The authors suggest that the endogenous retroviral insertion could offer protection against T1D, but they did not provide any functional relationship between the low copy numbers and the T1D susceptibility (59). Conversely, present results now clearly indicate the involvement of an endogenous retrovirus, HERV-W, in the pathogenesis of T1D.…”
Section: Endogenous Retroviruses In T1d Etiologycontrasting
confidence: 40%
“…Taken together, our genetic and expression analysis suggested that HNP1-3 may provide a protective effect against development of IgAN and the progression of renal dysfunction. 12 Interestingly, our study has also revealed a strong association of the DEFA1A3 CNV (211bp) with membranous nephropathy, but not diabetic kidney disease, although our diabetic kidney disease cohort had a bigger sample size and thus more power than did the membranous nephropathy cohort to detect the association. The genetic effect (OR) of 211bp consistent between membranous nephropathy (OR=0.74) and IgAN (OR=0.75) without evidence of heterogeneity (I 2 =0, Q test=0.84), suggesting the shared protective effect of 211bp variant against both membranous nephropathy and IgAN.…”
Section: Discussionmentioning
confidence: 95%
“…Although CNVs have been suggested to play important roles in disease development (10,12,13), the associations of CNVs, particularly the role complex multi-allelic CNVs may play in complex diseases, are poorly studied and understood, mainly due to experimental difficulties in measuring the copy number of such variants accurately (14).The -defensin locus (DEFA1A3) is one of the complex multi-allelic CNVs, presents as tandem repeats of a 19kb sequence unit, each of which contains one copy of DEFA1 or DEFA3(differing by a single non-synonymous coding variant within the third exon) as well as several internal bi-allelic polymorphisms (15)(16)(17). The protein products of DEFA1A3, HNP1-3 (human neutrophil peptide 1to 3), are the most abundant of neutrophil granule proteins, and there is evidence to suggest that neutrophils may play an important role in mediating glomerular injury in IgAN (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Additional and new techniques will be needed to detect these terminally deleted viruses in pancreata from pre-or diabetic individuals to ascertain their possible role(s) in the pathogenesis of T1D. Slow-replicating, endogenous and/or latent viruses like herpesviruses may also be good candidates, as they are commonly found in humans and can persist in the pancreas without exhibiting cytopathic effects (Marguerat et al 2004;Mason et al 2014;Ramondetti et al 2012). The MHC-I pattern shown here could match a possible lobular spreading of these viruses.…”
Section: Discussionmentioning
confidence: 99%